Antibiotic removal by metal–organic framework and 2D nanomaterial based polyetherimide mixed matrix membranes using a membrane bioreactor. Issue 1 (8th November 2022) - Sonawane, Amol Vijay; Murthy, Z. V. P.
Abstract : The ZIF-8, MoS2 and h-BN based PEI MMMs are fabricated to investigate their removal performance for antibiotics (favipiravir, ivermectin and azithromycin) using the MBR system. The MMMs show significant removal of antibiotics from synthetic wastewater. Abstract : In the present research work, a metal–organic framework (MOF) and 2-dimensional (2D) nanoparticles are incorporated into a polyetherimide (PEI) mixed matrix membrane to enhance their antibiotic removal performance using the submerged membrane bioreactor process. The zinc imidazolate framework (ZIF-8) (MOF) and molybdenum disulfide (MoS2 ) and hexagonal boron nitride (h-BN) as 2D nanomaterials have been used to enhance the structural, physical and mechanical properties of the PEI mixed matrix membranes. The different properties of the PEI mixed matrix membranes are studied using FTIR, XRD, FE-SEM, water contact angle, tensile strength, AFM and TEM analysis. Favipiravir, azithromycin and ivermectin are used as model antibiotics for the removal study. The prepared ZIF-8/PEI, MoS2 /PEI and h-BN/PEI mixed matrix membranes show significant removal of antibiotics such as 87.5%, 88.89% and 92.61% for favipiravir, azithromycin, and ivermectin, respectively. The antifouling performance of the PEI mixed matrix membranes is studied using a submerged membrane bioreactor. The h-BN/PEI mixed matrix membrane shows superior antifouling performance compared to other membranes. The stability and reusability performance of the prepared membranes are investigated. The results show that the h-BN/PEI mixed matrix membrane shows significant characteristics and long-term performance. From the overall study, it is found that the MOF and 2D nanomaterials in the PEI mixed matrix membranes have strong commercial potential for antibiotic wastewater treatment.